Analysis and Simulation of the Effect of Knee Structure on the Condylar Forces - Sadeghian, Farshaid; Davoudi, Mehrdad; Meftahi, Narges; Parnianpour, Mohamad; Karimpour, Morad (Journal of Clinical Physiotherapy Research, 2020)
The varus deformity of the femur and the tibia leads to an increase in the medial condylar force, which may result in osteoarthritis in the medial condyle, if left untreated. Through Medial Open Wedge Osteotomy for these patients, it is possible to realign the load bearing surfaces of the knee joint which can lead to the tightening of some of the ligaments between the femur and the tibia on the medial side, and it can generate an excessive force on the medial condyle. The correction angle of osteotomy determines how much force is removed from the medial condyle, due to the realignment of the joint, and how much force is exerted due to the tightening of the Medial Collateral Ligament. If the post-surgical force exerted on the medial condyle is greater than the force was before surgery, it can cause even further damage in the medial condyle. OpenSim was utilized to simulate patients with varus deformity as well as calculating the Condylar forces during the gait cycle. The objective of this research is to find the critical correction angle in varus-aligned knee joints for specific patient; the threshold of the correction angle at which the medial condylar force increases after surgery, due to ligament tightening. Medial condylar force of the knee and tension in the Lateral Collateral Ligament (LCL) and Popliteofibular Ligament (PFL) in a specific subject show that a scenario with a 76 degree Medial Proximal Tibial Angle (MPTA) corresponding to 14 degrees of deformity is a critical point beyond which the surgeon must perform an MCL release. Without releasing of MCL during High Tibial Osteotomy (HTO), increased tension in this ligament make greater force in medial condyle after the surgery.